Labour issues in hotels and their management: UK and Brexit - Mumford, Chris (Henry Stewart Talks, 2023)
Impact of Brexit on hospitality industry, Hotel relationship with employees, Pre vs. post Brexit statistics, Brexit and the hospitality workforce, The Gallivant hotel, Labour turnover